Gender diversity advantage at middle management: Implications for high performance work system improvement and organizational performance - Joo, Min‐Kyu; Lee, Jeong‐Yeon; Kong, Dejun Tony; Jolly, Phillip M. (Human Resource Management, 2023)
Abstract Research on women in leadership positions has largely focused on the board or top management team (TMT) leadership level, showing that increased female representation at these levels can benefit organizational performance. However, the strategic implications of female representation at middle management have been largely neglected. The current study addresses this issue in relation to High Performance Work System (HPWS) improvement and organizational performance (profitability). By analyzing the multi‐wave (2009, 2011, and 2013) Workplace Panel Survey (WPS) data collected from 1101 organizations in South Korea, we found a gender diversity advantage at middle management; that is, a higher level of gender diversity of middle management translated into a higher level of organizational performance due to HPWS improvement. However, this advantage appeared only in the presence of a high level of subordinates' gender diversity. Our findings have important implications for gender diversity and strategic human resource management.